Conogethes punctiferalis (Lepidoptera: Pyralidae) its biology and field parasitization - Stanley, J MARUTHI; Chandrasekaran, S; Preetha, G (The Indian Journal of Agricultural Sciences, 2011)
Conogethes punctiferalis Guenee was found to complete its life-cycle within a shorter period in castor, followed by cardamom, guava and ginger under laboratory conditions. The number of days taken by the neonate larva to become adult was 27.76 in castor and 30.69 days in cardamom, while it was 32.05 in ginger. Parasitoids, like Trathala flavoorbitalis Cameron, Brachymeria atteviae JNJ, Chelonus blackburni Cameron, Anthrocephalus decipiens (Masi), Epitranus erythrogaster Cameron and Phorids were found to parasitise C. punctiferalis larvae in castor crop. A unit increase in relative humidity resulted in 2.73% increase in damage by C. punctiferalis in castor, thus favouring the pest. A unit increase in rainfall resulted in 2.79% increase in parasitization by T. flavo-orbitalis, the major parasitoid on C. punctiferalis